2019
DOI: 10.1016/j.isci.2018.12.034
|View full text |Cite
|
Sign up to set email alerts
|

IFNG-AS1 Enhances Interferon Gamma Production in Human Natural Killer Cells

Abstract: SummaryLong, non-coding RNAs (lncRNAs) are involved in the regulation of many cellular processes. The lncRNA IFNG-AS1 was found to strongly influence the responses to several pathogens in mice by increasing interferon gamma (IFNγ) secretion. Studies have looked at IFNG-AS1 in T cells, yet IFNG-AS1 function in natural killer cells (NKs), an important source of IFNγ, remains unknown. Here, we show a previously undescribed sequence of IFNG-AS1 and report that it may be more abundant in cells than previously thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“… 38 , 39 It could also promote IFN-γ production in nature killer cells and suppress cancer progress. 40 It is suggested that the 8 lncRNAs could affect the immune response of CC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 It could also promote IFN-γ production in nature killer cells and suppress cancer progress. 40 It is suggested that the 8 lncRNAs could affect the immune response of CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cells are the major innate lymphocytes [ 11 , 12 , 13 , 14 ]. NK cells mediate cytotoxicity [ 15 , 16 , 17 , 18 , 19 ] and produce significant quantities of inflammatory cytokines, including interferon-γ (IFN-γ) [ 20 , 21 , 22 , 23 , 24 ] and tumor necrosis factor-alpha (TNF-α) [ 25 , 26 , 27 , 28 ]. Our knowledge about the molecular basis of the development and functions of NK cells is progressing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The long non-coding RNA Tmevpg1, also known as NeST or IFNG-AS1, has also been implicated in regulating IFNγ production 153 . A recent publication identified a unique Accepted Article isoform expressed in human NK cells that impacted IFNγ transcription and secretion 154 , indicating regulation on a transcriptional rather than translational level. NK cell receptor-mediated IFNγ production has been well established in in vitro models, but its role during virus infections in vivo remains largely unexplored.…”
Section: Accepted Articlementioning
confidence: 99%